Effect of Wall Inclination on Dynamic Active Thrust for Cohesive Soil Backfill - Gupta, A.; Yadav, V.; Sawant, V. A.; Agarwal, R. (Journal of Civil Engineering, Science and Technology, 2018)
Design of retaining walls under seismic conditions is based on the calculation of seismic earth pressure behind the wall. To calculate the seismic active earth pressure behind the vertical retaining wall, many researchers report analytical solutions using the pseudo-static approach for both cohesionless and cohesive soil backfill. Design charts have been presented for the calculation of seismic active earth pressure behind vertical retaining walls in the non-dimensional form. For inclined retaining walls, the analytical solutions for the calculation of seismic active earth pressure as well as the design charts (in non-dimensional form) have been reported in few studies for c-ϕ soil backfill. One analytical solution for the calculation of seismic active earth pressure behind inclined retaining walls by Shukla (2015) is used in the present study to obtain the design charts in non-dimensional form. Different field parameters related with wall geometry, seismic loadings, tension cracks, soil backfill properties, surcharge and wall friction are used in the present analysis. The present study has quantified the effect of negative and positive wall inclination as well as the effect of soil cohesion (c), angle of shearing resistance (ϕ), surcharge loading (q) and the horizontal and vertical seismic coefficient (kh and kv) on seismic active earth pressure with the help of design charts for c-ϕ soil backfill. The design charts presented here in non-dimensional form are simple to use and can be implemented by field engineers for design of inclined retaining walls under seismic conditions. The active earth pressure coefficients for cohesionless soil backfill achieved from the present study are validated with studies reported in the literature.